NMI and IFP35 serve as proinflammatory DAMPs during cellular infection and injury - Zhikai Xiahou (Nature Portfolio, 2017)
Damage-associated molecular patterns (DAMP) are important mediators of innate immunity. Here the authors show that N-myc and STAT interactor (NMI) and interferon-induced protein 35 (IFP35) act as DAMPs to promote inflammation by activating macrophages via the Toll-like receptor 4 and NF-κB pathways.